Toponymic Aspects of Caves in Central Buton Regency: Toponymic Study - Rizal; Riyadi Santosa; Wakit Abdullah Rais (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to reveal the origins of cave naming in Central Buton. This is carried out by classifying the aspects of toponymy, namely physical manifestation, social aspects, and cultural aspects, so that the close relationship between language, environment, and the culture of the local community can be demonstrated. This research uses a qualitative descriptive approach with inductive data analysis. The data were obtained through semi-structured interviews with traditional leaders and local community members who understand the history of the caves. The interviews were conducted using recording and note-taking techniques. The data were analyzed through qualitative thematic analysis. The results show that the physical manifestation aspect is reflected in cave names based on their physical conditions and environment, with 6 data findings. The social aspect appears in cave names associated with local figures, with 3 data findings. Meanwhile, the cultural aspect is present through community myths and legends, with 4 data findings. Thus, it can be understood that the toponymy of caves in Central Buton does not merely represent the identity of physical space but also functions as a living archive that records ecological knowledge, social memory, and the cultural heritage of the community.